Biological Therapy in Primary Sjögren's Syndrome: Effect on Salivary Gland Function and Inflammation - Chowdhury, Farzana; Tappuni, Anwar; Bombardieri, Michele (Frontiers in Medicine, 2021)
Primary Sjögren’s syndrome (pSS) is a chronic, systemic autoimmune disease. It is the second most common rheumatic autoimmune disorder, affecting 0.7% of European Americans and up to 1% of people globally. pSS is characterised by the impaired secretory function of exocrine glands, including salivary and lachrymal glands. A lymphocytic infiltration of these organs leads to the common and debilitating symptoms of oral and ocular dryness, majorly affecting the quality of life of these patients. Currently, no disease-modifying drug has been approved for the treatment of pSS, with therapies largely aimed at relieving symptoms of dry mouth and dry eyes. In particular, management of oral dryness still represents a major unmet clinical need in pSS and a significant burden for patients with this condition. Recently, several randomised clinical trials in pSS with biological therapies targeting specific mechanistic pathways implicated in the disease pathogenesis, including B-cell hyperactivity, T-cell co-stimulation and the aberrant role of cytokines, have been completed with mixed results. In this review, we summarise evidence from recent clinical trials investigating biological therapy in pSS, specifically highlighting efficacy, or lack thereof, in modulating local inflammation and improving salivary gland function.